Notes on the genus Parastasia Westwood (Coleoptera: Scarabaeidae: Rutelinae) from China, with description of a new species - Zhao, Ming-Zhi (Zootaxa, 2019)
Parastasia qiului Zhao, new species is described and illustrated from southwest China. This new species is allied to P. akebono Wada, 2015 from India, but can be easily distinguished from the latter by the differences of color pattern and the shape of aedeagus. Parastasia sawadai Wada, 2003, P. alternata Arrow, 1899, and P. indica Ohaus, 1898 are reported new to Chinese fauna. Additional records for P. oberthueri Ohaus, 1900 and P. birmana Arrow, 1899 are provided. The knowledge of the natural history in this genus is improved.